New di(hetero)arylethers and di(hetero)arylamines in the thieno[3,2-b]pyridine series: Synthesis, growth inhibitory activity on human tumor cell lines and non-tumor cells, effects on cell cycle and on programmed cell death - Queiroz, Maria João R. P. (2013)
New fluorinated and methoxylated di(hetero)arylethers and di(hetero)arylamines were prepared functionalizing the 7-position of the thieno[3,2-blpyridine, using copper (C-O) or palladium (C N) catalyzed couplings, respectively, of the 7-bromothieno[3,2-blpyridine, also prepared, with ortho, meta and para fluoro or methoxy phenols and anilines. The compounds obtained were evaluated for their growth inhibitory activity on the human tumor cell lines MCF-7 (breast adenocarcinoma), NCI-H460 (non-small cell lung cancer), HCI15 (colon carcinoma), HepG2 (hepatocellular carcinoma) and HeLa (cervical carcinoma). The most active compounds, a di(hetero)arylether with a methoxy group in the meta position relative to the ether function and two di(hetero)arylamines with a methoxy group either in the ortho or in the meta position relative to the NH, were further tested at their GI(50) concentrations on NCI-H460 cells causing pronounced alterations in the cell cycle profile and a strong and significant increase in the programmed death of these cells. The fluorinated and the other methoxylated compounds did not show important activity, presenting high GI(50) values in all the cell lines tested. Furthermore, the hepatotoxicity of the compounds was assessed using porcine liver primary cells (PLP2), established by some of us. Results showed that one of the most active compounds was not toxic to the non-tumor cells at their GI(50) concentrations showing to be the most promising as antitumoral.